Studying The Role Of Cartilago Oligomer Matrix Protein (Comp) In Joint Structure Changes In Osteoarthritis (Texas Journal of Medical Science, 2024)
To study the role of cartilage oligomeric matrix protein in structural changes in joints in patients with osteoarthritis (OA). Material and methods: We observed 50 patients diagnosed with osteoarthritis aged 54.5±4.4 years, of whom 43.8% had radiographic stage 0, 40% had stage I, and 16.2% had stage II. Patients in the main group received treatment aimed at reducing the amount of cartilage oligomeric matrix protein, while patients in the control group received traditional treatment. Results: In addition to clinical improvement and a decrease in the intensity of pain in the knee joint, patients in the main group also had lower levels of SOMP, CRP, and ESR in the blood serum compared to patients in the control group. Conclusions: The treatment method aimed at the dynamics of COMP differs from the traditional one in that it is aimed at suppressing the reactions of cartilage destruction in OA